Effects of dynamic upper-body exercise on lower-limb isometric endurance - Easton, C.; Findlay, C.; Morrison, G.; Sourway, N. C. (Journal of Sports Sciences, 2007)
Following preliminary indications that in some individuals arm exercise enhanced rather than reduced simultaneous leg endurance, ten young men and women performed three forms of intermittent work to volitional exhaustion, under duty cycles of 45 s work, 15 s rest. The protocols were as follows: (A) knee extensions at 30% maximum voluntary contraction (MVC); (B) 30% MVC knee extensions combined with arm cranking at 130% of their own lactate threshold; (C) combined 30% MVC knee extensions and arm cranking at 20% of their own lactate threshold. Heart rate, oxygen uptake (O2), and blood lactate concentration were among the variables recorded throughout. All physiological indicators of demand were substantially higher in protocol B than in protocols A or C [heart rate: (A) 154 beats · min-1, (B) 171 beats · min-1, (C) 150 beats · min-1; O2: (A) 11.9 ml · kg-1 · min-1, (B) 21.7 ml · kg-1 · min-1, (C) 14.2 ml · kg-1 · min-1; blood lactate concentration: (A) 3.3 mmol · l-1, (B) 5.1 mmol · l-1, (C) 2.8 mmol · l-1], yet there were no significant differences (P > 0.05) in the endurance times between the three conditions [(A) 11.43 min, (B) 11.1 min, (C) 10.57 min] and seven participants endured longest in protocol B. Results from protocol (C) cast doubt on explanations in terms of psychological distraction. We suggest that lactic acid produced by the arms is shuttled to the legs and acts there either as a supplementary fuel source or as an antagonist to the depressing effects of increased potassium concentration.